Strategi Brand Compass dalam Membangun Niat Beli Konsumen - Farel Kyla Riswanda; Arfian Suryasuciramdhan; Zulhanderi Zulhanderi; Budi Hermawan; Rizky Arian Maulana (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study explores how the branding strategy of COMPASS’s, a local fashion brand, shapes consumer perceptions and influences their purchase intentions. Employing a qualitative case study approach, the research examines key elements of COMPASS’s brand strategy, including visual identity, storytelling, and digital communication. The findings highlight the brand’s ability to maintain a consistent image, align products with market trends, and foster emotional connections with its audience. Additionally, market appeal such as exclusivity, community engagement, and lifestyle relevance emerges as a significant factor in encouraging consumer intention to buy. The study aims to offer practical insights for other local fashion brands in crafting more focused and consumer-oriented branding strategies.